Democratic religion from Locke to Obama : faith and the civic life of democracy - Areshidze, Giorgi, 1983- (American political thought., 2016)
Debating or making speeches, American politicians invariably cite tenets of Christian faith-even as they unfailingly defend the liberal principles of tolerance and religious neutrality that underpin a pluralistic democracy. How these seemingly contradictory impulses can coexist-and whether this undermines the religious tradition that makes a liberal democracy possible-are the pressing questions that Giorgi Areshidze grapples with in this exploration of the civic role of religion in American political life. The early modern Enlightenment political philosophy of John Locke has been deeply influen.